2008
DOI: 10.1111/j.1365-2435.2008.01453.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing the correlations between leaf life span and leaf structural reinforcement in 13 species of European Mediterranean woody plants

Abstract: Summary 1.It has been proposed that in longer-living leaves the allocation of biomass to structural components is greater than in shorter-living leaves, leading to a greater leaf mass per area (LMA) and to lower assimilation rates. However, direct evidence in support of this hypothesis is very scarce. 2. In the present work we investigated the relationships between leaf duration and LMA, leaf thickness and fibre concentrations (cellulose, hemicellulose and lignin) in five oak species, five pine species and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 59 publications
2
57
1
1
Order By: Relevance
“…Conversely, this negative relationship is not consistent with previous results [32]. As one of the most variable plant characteristics affecting major physiological properties that enable plants to adapt to numerous environmental conditions [9,33], such as defense against pathogens [23] and herbivores [9], leaf shape index was positively correlated with petiole diameter, leaf length, leaf thickness, ratio of leaf length to petiole length, ad single leaf wet and dry weight, but negatively correlated with leaf moisture. Therefore, leaf shape index may be affected by leaf length, leaf thickness, allocated biomass in leaf lamina relative to leaf petiole (the ratio of leaf length to petiole length), a single leaf wet and dry weight (although leaf shape index was calculated as the ratio of leaf length to the corresponding leaf width).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Conversely, this negative relationship is not consistent with previous results [32]. As one of the most variable plant characteristics affecting major physiological properties that enable plants to adapt to numerous environmental conditions [9,33], such as defense against pathogens [23] and herbivores [9], leaf shape index was positively correlated with petiole diameter, leaf length, leaf thickness, ratio of leaf length to petiole length, ad single leaf wet and dry weight, but negatively correlated with leaf moisture. Therefore, leaf shape index may be affected by leaf length, leaf thickness, allocated biomass in leaf lamina relative to leaf petiole (the ratio of leaf length to petiole length), a single leaf wet and dry weight (although leaf shape index was calculated as the ratio of leaf length to the corresponding leaf width).…”
Section: Discussioncontrasting
confidence: 62%
“…This high material investment per unit area is necessary to yield low leaf moisture and SLA, but high leaf thickness, single leaf wet weight, and single leaf dry weight compared with the results described in previous studies [7,[14][15]. Furthermore, leaves with low SLA contain more ructural carbohydrates, such as lignin and cellulose in their cell walls , than those with high SLA [23]. Consistent with the first hypothesis, our results showed that leaf moisture and SLA of damaged leaves were significantly lower than those of healthy leaves.…”
Section: Discussionmentioning
confidence: 66%
“…The density of leaf lamina is influenced by the packing of cells and by the thickness and composition of the cell walls and, to a lesser extent, by the composition of the protoplasts. Evergreen leaves tend to be both thicker and denser than deciduous leaves (Mediavilla et al 2001;Mediavilla et al 2008;Poorter et al 2009; see Fig. 1 A vs. B, E vs. F) with much interspecific variability (Rotondi et al 2003;Villar et al 2013).…”
Section: Anatomy and Morphologymentioning
confidence: 99%
“…Chemical analyses of evergreen leaves usually yield higher cellulose and hemicellulose concentrations, and, often but not always, a higher lignin concentration compared to deciduous species (Villar and Merino 2001;Mediavilla et al 2008). The metabolic cost per unit of leaf biomass has been estimated by measuring the heat of combustion corrected for ash content and additionally calculating the cost of protein synthesis (Villar and Merino 2001).…”
Section: Construction Costsmentioning
confidence: 99%
“…for [59] or 155 gC m −2 for [60]). This supports our statement of a well-watered site based on the observed plasticity of this functional trait according to drought [61,62].…”
Section: Bellif Ecosystem Peculiar Fertile Conditions Within the Medimentioning
confidence: 99%